2012
DOI: 10.1186/1471-2458-12-752
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and dietary intake of urban residents in Gondar, Northwest Ethiopia

Abstract: BackgroundThere is paucity of data on the dietary intake and nutritional status of urban Ethiopians which necessitates comprehensive nutritional assessments. Therefore, the present study was aimed at evaluating the dietary intake and nutritional status of urban residents in Northwest Ethiopia.MethodsThis cross-sectional community based nutrition survey was conducted by involving 356 participants (71.3% female and 28.7% male with mean age of 37.3 years). Subjects were selected by random sampling. Socio demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 25 publications
6
67
4
Order By: Relevance
“…In Ethiopia, studies have shown a higher prevalence of malnutrition among lactating women [11]. A study conducted in Northwest Ethiopia showed nutritional inadequacy among urban residents [12]. The 2011 Ethiopian demographic and health survey (EDHS) report showed that 27% of women aged 15-49 years were undernourished.…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, studies have shown a higher prevalence of malnutrition among lactating women [11]. A study conducted in Northwest Ethiopia showed nutritional inadequacy among urban residents [12]. The 2011 Ethiopian demographic and health survey (EDHS) report showed that 27% of women aged 15-49 years were undernourished.…”
Section: Introductionmentioning
confidence: 99%
“…Hence there is causation between nutrition status and labour productivity or wage (Nuwaha et al, 2011;McNamara et al, 2012;Basta et al, 1979;Deolalikar, 1988). However, nutritional measure such as calorie, protein, and iron intake being the input of health production function do not have reverse causation with the health of individual (Strauss, 1986;Amare et al, 2012;Dalgaard and Strulik, 2011;Wang et al, 2014).…”
Section: Second Reverse Causation Of Wage On Nutrition Intake and Mementioning
confidence: 99%
“…Dietary intake determines the nutrition status (Amare et al, 2012) and nutrition status has an effect on health outcome such as morbidity and mortality in a population (Shankar, 2000;Ulijaszek, 1996;Caulfield et al, 2004;Katona and Katona-Apte, 2008;Black et al, 2008); and individual health determine the labour efficiency, wage and productivity (Sachs, 2001;Alleyne and Cohen, 2002;Behrman, 1993;Deolalikar, 1988;Behrman et al, 1988). Hence there is causation between nutrition status and labour productivity or wage (Nuwaha et al, 2011;McNamara et al, 2012;Basta et al, 1979;Deolalikar, 1988).…”
Section: Second Reverse Causation Of Wage On Nutrition Intake and Mementioning
confidence: 99%
See 2 more Smart Citations